Brave new words how AI will revolutionize education and why that's a good thing - Khan, Salman (New York Viking, 2024)
A pioneer in the field of education technology, Khan examines the ins and outs of these cutting-edge tools and how they will revolutionize the way we learn and teach. For parents concerned about their children$1 (Bs success, Khan illustrates how AI can personalize learning by adapting to each student$1 (Bs individual pace and style, identifying strengths and areas for improvement, and offering tailored support and feedback to complement traditional classroom instruction. Khan emphasizes that embracing AI in education is not about replacing human interaction but enhancing it with customized and accessible learning tools that encourage creative problem-solving skills and prepare students for an increasingly digital world.s
Includes bibliographical references and index.
Keywords: Artificial intelligence--Educational applications. Educational change. Education--Parent participation